Project-Based Learning counseling guidance in restoring student learning motivation after Covid-19 - Nur, Edil Wijaya (International Journal of Applied Guidance and Counseling, 2022)
The implementation of PTMT which began to be rolled out by the government in several schools turned out to have problems in the early days of student learning. BDR system leaves a psychological phenomenon in the form of learning loss which boils down to decreased student motivation in the classroom. The author as a teacher who acts as a facilitator BK students take the initiative to implement Project-Based Learning as an effort to internalize the character of the Pancasila student profile into each student so that it can re-trigger student learning motivation with a more student-centered learning model and atmosphere. The argument in this paper is built with the perspective of Best Practice teachers to restore student learning motivation lost during BDR. The results of this activity concluded that (1) Project Based Learning is worth using as a good practice for guidance and learning because it can restore student motivation that has decreased after the COVID-19 pandemic. (2) with Project-Based Learning, we can internalize the character of the Pancasila student profile with a pattern of integration and more fun.